Digital Diplomacy Regulations And Policies: The Middle Power Country's Approach As Indonesia's Multilateral Strategy - Evi Dwi Hastri; Imam Hidayat; Imam Rofiqi (International Journal of Law, Crime and Justice, 2024)
Countries in the Indo-Pacific region are increasingly actively using digital diplomacy to build relationships Countries use digital diplomacy by referring to foreign regulations and policies used for countries in conducting multilateral diplomacy, namely the 1964 Vienna Convention on Diplomatic Relations. Apart from the main guidelines that have arisen, the main problem arises, namely in the practice of international relations, is the lack of regulations and arrangements for digital diplomacy practices for middle power countries such as Indonesia who want to strengthen their role in supporting their country's defense and security. By using the type of normative legal research and the analysis approach, this study produces findings that the need for regulations and arrangements for digital diplomacy that can support Indonesia's role in strengthening the country's defense and security